Web And Mobile Based Fakulti Komputeran Hybrid Attendance System(Fkhas) With Implementation Of Rfid And Qr Technology - Sitha, Gunasegran (2023)
The aim of this project is to develop Web and Mobile Based Fakulti Komputeran Hybrid Attendance System (FKHAS) With Implementation Of RFID And QR Technology. The users of the system are admin, FK lecturer, and students. This system helps the users to manage FK student’s attendance system. This system consists 6 of modules. Not only that, but this system also implements RFID technology and QR code for recording attendance data. Students who are in campus can use RFID card scanning to record their attendance. Meanwhile students who at their hometown and attending classes online mode can update their attendance by scanning QR code based on the event they have assigned. Admin and lecturer can view the student’s attendance based on the class mode.